Xiaoyaosan formula augments adjuvant therapy and enhances postoperative breast cancer care - Wang, Chao; Yin, Lianfang (Frontiers in Pharmacology, 2024)
Objective: Xiaoyaosan (XYS), a traditional Chinese formula, not only has good antitumour effects but also attenuates distress, anorexia, and quality of life (QoL) by regulating neurology, the microbiota, immunology and oxidative stress. This study aimed to assess the effect of XYS on QoL, psychological pressure, and spiritual well-being in breast cancer patients undergoing adjuvant chemotherapy. Methods: This prospective cohort study enrolled 176 postoperative breast cancer patients who received adjuvant chemotherapy combined with (n=81) or without (n=95) XYS for comparison. The Quality-of-Life Questionnaire Core-30 (QLQ-C30), Hospital Anxiety and Depression Scale (HADS), University of California Los Angeles (UCLA-LS), and Functional Assessment of Chronic Illness Therapy-Spiritual Well-being (FACIT-Sp) scores were evaluated before adjuvant chemotherapy (T0) and after the 1st (T1), 2nd (T2), 3rd (T3), and 4th cycles (T4) of adjuvant chemotherapy. Results: XYS improved the QLQ-C30 score at T2 (P=0.043), T3 (P=0.021), and T4 (P=0.040) and the QLQ-C30 score at T4 (P=0.027); moreover, XYS attenuated the QLQ-C30 score at T2 (P=0.040), T3 (P=0.023), and T4 (P=0.027). Regarding distress, XYS reduced the HADS-anxiety score at T2 (P=0.010), T3 (P=0.025), and T4 (P=0.019) and the HADS-defined anxiety score at T3 (P=0.038). XYS also decreased the HADS-depression score at T2 (P=0.016), T3 (P=0.018), and T4 (P=0.017) and the HADS-defined depression rate at T2 (P=0.047), T3 (P=0.012), and T4 (P=0.013). In addition, XYS decreased the UCLA-LS at T2 (P=0.023) but enhanced the FACIT-Sp at T2 (P=0.029) and T4 (P=0.026). Furthermore, after adjustment via propensity score matching, most of the significant findings remained. Conclusion: The addition of XYS to adjuvant chemotherapy improved QoL, psychological health, and spiritual well-being in breast cancer patients.